(untitled) (Conferencea, 2023)
Behavioral, biological, hereditary, social, environmental and occupational risk factors, which are considered risk factors for health in the formation and development of the most important socially significant diseases, increase the likelihood of developing diseases, play a major role in their development and leading to negative consequences. Proper nutrition is considered one of the main requirements for strengthening human health and is recognized as a determining factor in the state of health of individual and collective groups. Following a healthy lifestyle, including exercise, proper nutrition, quitting smoking, controlling blood pressure, blood glucose, and protein levels, are important factors that can help reduce the development of kidney disease. For patients with typical kidney disease, the protein in food ration is 0.6 g per 1 kg of body weight per day, and at least 50% of them should be made up of products of high biological value, such as eggs, fish and meat. The main part of the daily strength should be replenished at the expense of carbohydrates (55-60% of the total strength) and fats (30-35% of the total strength). Due to the restriction of protein-rich foods (dairy and semi-finished foods), this diet is usually low in phosphorus (600-800 mg per day), sodium (2-3 g per day) and calcium.